Evaluating the proficiency of a novel solar evacuated tube collector. (25th May 2023) - Yang, Xingxing; Lin, Qing; Singh, Pavitra; Riaz, Fahid; Agrawal, Manoj Kumar; Alsenani, Theyab R.; Xia, Guangqiang Li; Abdelmohimen, Mostafa A.H.
Graphical abstract: Highlights: A novel solar evacuated tube collector combined with a photovoltaic cell is proposed. Adding metal foam improves the performance of the system significantly. Increasing the melting point has an adverse effect on the outputs of the system. Raising the mass flow rate enhances the electrical and thermal outputs of the system. Dispersing nanoparticles boosts the power generation of the system. Abstract: Evacuated tube collector is a type of solar energy unit that converts solar energy into thermal power; however, the output of this unit is not high. Therefore, the present research attempted to propose a highly efficient unit to transform solar energy into proper forms of energy, including electrical and thermal. In the current numerical study, initially, the overall proficiency of integration of the phase change material in the evacuated tube solar collector is poked and compared with the performance of a maiden renewable-based unit consisting of an evacuated tube collector, photovoltaic module, phase change material, and porous metal foam. Henceforth, by determining the best unit from the overall energy viewpoint, the impact of various factors, including melting temperature of phase change material, nanoparticle mass fraction, and mass flow rate of operating fluid on the operation of the unit, are investigated. According to the obtained results, the evacuated tube collector equipped with the photovoltaic module, phase change material, and porous metal foam has the highest performance among the studied units from the energy viewpoint. The overall performance of the presented unit is calculated to be 13 % higher than the net efficiency of conventional evacuated tube solar collector. It is observed that boosting the mass flow rate of operating fluid from 3.6 to 10.8 L/h enhances the average overall output of the presented unit from 38.55 W to 40.13 W. Reducing the melting point of the phase change material can slightly boost the performance of the unit; according to the simulations, reducing the melting point from 44 °C to 35 °C raises the overall performance of the unit by around 0.4 %. Also, dispersing nanoparticles in the base fluid improves the performance of the unit by 3.3 %.